Wire localization of clip-marked axillary lymph nodes in breast cancer patients treated with primary systemic therapy. Issue 9 (September 2018) - Hartmann, Steffi; Reimer, Toralf; Gerber, Bernd; Stubert, Johannes; Stengel, Bernd; Stachs, Angrit
Abstract: Introduction: Clipping and selective removal of initially suspicious axillary lymph nodes in breast cancer patients who have been sonographically down-staged by primary systemic therapy improves the accuracy of surgical staging and provides the opportunity for more conservative axillary surgery. This study evaluated whether preoperative ultrasound-guided wire localization of the clipped node is useful for routine clinical practice. Material and methods: This prospective, single-center feasibility trial included patients with invasive breast cancer (cT1-3N1-3M0) treated by primary systemic therapy. They underwent ultrasound-guided core needle biopsy and clip placement into the most suspicious axillary lymph node prior to chemotherapy. After primary systemic therapy the clipped lymph node was localized by a wire. All patients underwent target lymph node biopsy, completion axillary lymph node dissection and, if yiN0, axillary sentinel lymph node biopsy. The primary study endpoint was the identification rate of the target lymph node. Results: All patients (n = 30) underwent successful clip insertion into the lymph node. After chemotherapy, the clipped target lymph node was visible by ultrasound in 83.3% (25/30). Wire localization was possible in 24 cases (80%), and the clipped node identification rate was 70.8% (17/24 cases). In 9/30 patients (30%) clipped node removal was not confirmed by intraoperative radiography. Conclusion: Ultrasound-guided wire localization of the target lymph node is not suitable for clinical practice because of limitations regarding clip visibility and selective surgical preparation of the target lymph node. Further prospective evaluation of alternative techniques is needed.